The phenomenon of the city: socio-cultural dimension - O. D. Rykhlytska (Ukrainian Cultural Studies, 2019)
The article deals with theoretical and practical analysis of modern approaches to the study of the city and urban culture, which in the study is understood as a special phenomenon that ontologically determines the form and content of cultures in various manifestations of socio-cultural practice: physical, symbolic, mental. That is, a special space of embodiment of the semantic and symbolic needs and interests of human cultural activity. Modern processes of globalization and the rapid development of cities are definitely changing the role of the city, its space, affect cultural traditions, creative subjects of culture, innovative practices and cultural policy in general. The change in the semantic dominant and functions of the city is reflected in the search for a special urban space and culture, which are certain symbols of urban identity and their influence in general on the infrastructure of cities, urban rhythm of life, creation of architectural structures, etc. Particular attention is paid to the factors that influence the development of the city and urban culture, it is the loss of special relationships be- tween people, urban space and the environment, as well as the mechanisms of transfer of cultural heritage, as a symbol of collective aspirations, values. It is argued that the uncontrolled growth, glut, growth of industrial relations, consumer character and the leveling of the value basis of human interaction, the feeling of alienation, the growth of violent activity, as well as artificial modeling of urban space and destruction of the environment, are not only evidence of "absolute indifference" of the cities but also the devastating changes in the cultural and symbolic system of the city. In such a torn apart, polycentric world of the modern city ("techno cities", "exemplary ghost cities" "cyborg-cities"), a person loses rational integrity and psychological stability, and needs more harmonious techno-natural and cultivated space. There has been demonstrated the experience of harmonious construction of urban environment (E. Howard’s "garden-city", "zoo policy") and various practices ("ecology of culture", "visual ecology", etc.) of creation, and its influence on interpersonal interaction that requires significant sociocultural transformations. The progressive development of the city and urban culture is creating new conditions for socio-cultural development. Which in a certain way requires dramatic changes in the creation of a harmonious urban space and the reproduction of the diversity of cultural habitat, the creation of the unified natural-semiotic environment.